2022
DOI: 10.3389/fphar.2022.1030642
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of empagliflozin in heart failure patients with reduced and preserved ejection fraction in China

Abstract: Objective: EMPEROR-Reduced and EMPEROR-Preserved studies showed the benefits of empagliflozin along with a reduction in cardiovascular death or hospitalisation for heart failure (HF). Our aim was to evaluate the economics and effectiveness of adding empagliflozin to the standard therapy for HF with reduced ejection fraction (HFrEF) and HF preserved ejection fraction (HFpEF) in China.Methods: A multistate Markov model was constructed to yield the clinical and economic outcomes of adding empagliflozin to the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
(64 reference statements)
2
15
0
Order By: Relevance
“…dapagliflozin was more cost-effective) for patients with HF with lower stratifications of LVEF. This finding aligns with the outcomes presented by Tang et al 28 and Hallinen et al 29 in their investigations of empagliflozin across the spectrum of HF, although it is important to note that both studies used separate models for the HF with reduced and preserved ejection fraction populations and weighted averaging to generate a result for the overall HF population. In terms of clinical events, model predictions according to LVEF were also in line with clinical trial results, where event rates for recurrent HHF and CV death were observed to be higher for HF with reduced ejection fraction than for HF with preserved ejection fraction.…”
Section: Discussionsupporting
confidence: 86%
“…dapagliflozin was more cost-effective) for patients with HF with lower stratifications of LVEF. This finding aligns with the outcomes presented by Tang et al 28 and Hallinen et al 29 in their investigations of empagliflozin across the spectrum of HF, although it is important to note that both studies used separate models for the HF with reduced and preserved ejection fraction populations and weighted averaging to generate a result for the overall HF population. In terms of clinical events, model predictions according to LVEF were also in line with clinical trial results, where event rates for recurrent HHF and CV death were observed to be higher for HF with reduced ejection fraction than for HF with preserved ejection fraction.…”
Section: Discussionsupporting
confidence: 86%
“…The cost per QALY gained was $11 809 in Thailand with a lower WTP ($4773.27/QALY), which empagliflozin was not a cost‐effective add‐on treatment for patients with HFpEF 38 . We previously reported the pharmacoeconomics advantage of empagliflozin in HFrEF and HFpEF in China 41 . Additionally, several studies have shown that dapagliflozin was cost‐effective in the treatment of diabetes 42,43 Therefore, adding dapagliflozin to standard therapy was a cost‐effective choice for HFpEF and HFmrEF patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…38 We previously reported the pharmacoeconomics advantage of empagliflozin in HFrEF and HFpEF in China. 41 Additionally, several studies have shown that dapagliflozin was cost-effective in the treatment of diabetes 42,43 Therefore, adding dapagliflozin to standard therapy was a cost-effective choice for HFpEF and HFmrEF patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Another SGLT2 inhibitor, dapagliflozin, also showed a good cost‐effectiveness compared with SoC alone in patients with HFpEF in perspectives from a Chinese public healthcare 36 and public payers in European countries 37 . They assessed the cost‐effectiveness of dapagliflozin added to SoC compared with SoC alone based on the Dapagliflozin Evaluation to Improve the Lives of Patients with Preserved Ejection Fraction Heart Failure (DELIVER) trial, which was a placebo‐controlled trial in chronic HF patients with left ventricular ejection fraction > 40% that demonstrated a significant improvement in the combined incidence of HHF and CV death in patients treated with dapagliflozin added to SoC 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In the 2022 AHA/ACC/HFSA guidelines, a value statement is also described and the importance of analysis from the cost‐effectiveness perspective has been increasing globally 7 . There are prior studies that evaluated the cost‐effectiveness of SGLT2 inhibitors for patients with HFpEF 8–14 . However, in Japan, there is limited evidence of cost‐effectiveness for some types of HF medication (e.g.…”
Section: Introductionmentioning
confidence: 99%